(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Effect of Government Expenditure in Agricultural Sector and Local Original Revenue on The Gross Regional Domestic Product of The Agricultural Sector in Tabanan Regency, Bali Province. Tabanan Regency is located in Bali Province. Tabanan Regency, which is supported by its geographical and astronomical location, makes the agricultural sector a leading sector in its economy. The role of the government in developing the agricultural sector is reflected in the management of regional finances in the form of government expenditures in the agricultural sector and local original revenue to support activities in the agricultural sector. This study aims to analyze the effect of government expenditure in the agricultural sector and local original revenue on the GRDP of the agricultural sector in Tabanan Regency, Bali Province.This study used secondary data obtained from the Agriculture Office of Tabanan Regency, the Regional Finance Agency of Tabanan Regency, and the Central Statistics Agency of Tabanan Regency. The data used comes from 2010 to 2021 or within the last 12 years. To achieve this goal, the analysis method used in this study was to use multiple linear regression analysis with the IBM SPSS 25 program. The results of this study show that the variable of government expenditure in the agricultural sector affects the GRDP of the agricultural sector in Tabanan Regency, Bali, while the variable of local original revenue does not affect the GRDP of the agricultural sector in Tabanan Regency, Bali. The variables of government expenditure in the agricultural sector and local original revenue jointly affect the GRDP of the agricultural sector in Tabanan Regency in 2010-2021.